Pengembangan Model Layanan BK Terintegrasi: Mediasi, Konsultasi, dan Advokasi dengan Kegiatan Pendukung BK untuk Meningkatkan Kualitas Pendidikan - Cici Saputri; Rodia Rotani Rianda; M.Ari Khairan; Aida Efendy; Hanestesia Zahara; Revi Yulianti; M.Iqbal Ramadhan (Jurnal Budi Pekerti Agama Islam, 2025)
This journal discusses guidance and counseling service models as well as BK support activities to improve the quality of education. This research aims to build an integrated Guidance and Counseling (BK) service model, which combines mediation, consultation and advocacy methods, supported by additional BK activities to improve the quality of education in schools. So far, BK services have largely focused on individual approaches without any integration of strategic functions that can strengthen the entire education ecosystem. The model created in this study is aimed at strengthening the role of guidance and counseling teachers in handling student dynamics and building collaboration with the school, parents and the community. The research methodology uses a Research and Development (R&D) approach which includes needs analysis steps, model design, validation by experts, and limited trials in a secondary school environment. Research findings show that this integrated guidance and counseling service model is feasible to implement and effective in increasing the involvement of all parties in solving student problems and creating a school atmosphere that is more supportive of improving the quality of learning. The impact of this model opens up opportunities to increase the strategic role of guidance and counseling services in the education system as a whole.